Isolated Cardiac Metastasis from Squamous Cell Esophageal Cancer. Issue 4 (July 2015) - Abbate, Maria Ida; Cicchiello, Federica; Canova, Stefania; Cortinovis, Diego; Mariani, Silvia; Maffini, Fausto; Bidoli, Paolo
Although heart metastases are uncommon and generally a sign of disseminated disease, they are up to 40 times more frequent than primary cancers of the heart, and typically arise from melanoma or primary mediastinal cancer, but also from lymphoma, breast cancer, esophageal cancer, and leukemia. They are usually asymptomatic and found only at autopsy. Symptomatic patients generally die within a few weeks of diagnosis and usual treatments are chemotherapy, radiotherapy, or both. Surgical resection is recommended only for a single lesion, which is rare. We describe a 49-year-old man treated for squamous cell cancer of the esophagus in whom a single asymptomatic left heart metastasis was discovered incidentally during follow-up. The lesion was debulked surgically and multimodal treatment followed. The patient survived 1 year after diagnosis with good performance status during which time no other lesion was discovered. Cardiac metastasis is challenging and necessitates skilled multidisciplinary management to maximize the clinical outcome.